2022
DOI: 10.36349/easjpid.2022.v04i02.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Giardia lamblia and Cryptosporidium parvum co-infections among young adults in a private University in South-Western Nigeria

Abstract: Background: Giardia lamblia and Cryptosporidium parvum are major causes of diarrhoeal diseases of humans worldwide and are included in the World Health Organization’s ‘Neglected Diseases Initiative’. Aim: This research was designed to assess the prevalence of G. lamblia and C. parvum co-infections among undergraduate Students of Babcock University, Ilishan-Remo, Ogun State, Nigeria. Methods: An aggregate of 120 faecal specimens were obtained from 120 partakers (60 females and 60 males) who met the inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Among the children positive for Cryptosporidium , 18.2% (16/88) were coinfected with Giardia . This is in line with several other studies that reported low to no coinfections of these parasites [ 23 25 ]. In contrast, other studies have reported a much higher prevalence of coinfections, ranging from 8.7% to almost 30% [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among the children positive for Cryptosporidium , 18.2% (16/88) were coinfected with Giardia . This is in line with several other studies that reported low to no coinfections of these parasites [ 23 25 ]. In contrast, other studies have reported a much higher prevalence of coinfections, ranging from 8.7% to almost 30% [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%